The late Paleozoic to Mesozoic evolution of the eastern margin of the Central Asian Orogenic Belt in China - Wilde, Simon; Zhou, J. (Elsevier Ltd, 2015)
© 2015 Elsevier Ltd. The north-east Central Asian Orogenic Belt (CAOB) in China records terminal closure of the Paleo-Asian Ocean in the mid- to late Permian along the Solonker-Xar Moron-Changchun suture. This marks the end of the overall northward movement of the Chinese blocks from a peri-Gondwana position toward Siberia and a switch in tectonic processes to those dominated by activity associated with the Paleo-Pacific plate to the east. Four distinct changes in tectonic regime can be recognised here in the late Paleozoic to early Mesozoic: (i) north-south compression resulted in orogenesis and gave way to post-collisional extension at ~260-250. Ma with the emplacement of A-type granites; (ii) almost coeval with this, there was an the onset of east-west extension from 250 to 225. Ma along the extreme eastern margin of the CAOB, when a seaway opened between the Songliao and Jiamusi/Khanka blocks; (iii) the onset of westerly-directed compression, associated with subduction of the Paleo-Pacific plate from ~210. Ma, resulted in re-amalgamation of the Jiamusi/Khanka block with the CAOB by ~190-180. Ma and the massive generation of Jurassic I-type granitoids throughout the region; finally (iv) a change to east-west extension from ~140. Ma onward resulted from roll-back of the Paleo-Pacific plate. This latter event was accompanied by the emplacement of S-type granitoids and the development of sedimentary basins and core complexes. It also accompanied a more widespread thinning or delamination of the lithosphere across most of north-east China during the Cretaceous.